The application of artificial intelligence technology in tourism planning design - Wan Mohamed, Nik Rozilaini (2024)
The application of artificial intelligence in the tourism planning design has significantly transformed the way tourism planning designer and delivered their ideas. By integrating AI technologies such as sentiment analysis with Natural Language Processing (NLP), augmented reality, virtual reality, robotics in tourism planning design and intelligent chat bots, the tourism sector has witnessed a remarkable shift towards personalization and accurate recommendations for design planning students. Since the term "artificial intelligence" was first coined in 1956, there has been a clear link between artificial intelligence and interactive art. This connection is rooted in the inherent relationship between computer technology and art (Sanchez, et al, 2022).